2013
DOI: 10.1017/s0950268813001179
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated prevalence ofToxoplasma gondiiin 8281 pregnant women in Poland between 2004 and 2012

Abstract: This study aimed to describe Toxoplasma gondii prevalence in Polish pregnant women and the incidence rates of congenital infections in their neonates observed between 2004 and 2012. Serological tests for T. gondii-specific IgG and IgM antibodies were performed on serum samples of 8281 pregnant women treated at the Polish Mother's Memorial Hospital Research Institute in Lodz. The yearly seroconversion rate for T. gondii IgG antibodies was estimated using a mathematical model to determine the dependency between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 27 publications
5
21
1
Order By: Relevance
“…Some previous reports indicated that the seropositivity of T. gondii was related to age [9,10]. Consistent with these studies, the present study showed highly significant differences in T. gondii seropositivity in the different age groups (18-45, 45-65, >65 years) in the two ethnic populations.…”
Section: Discussionsupporting
confidence: 91%
“…Some previous reports indicated that the seropositivity of T. gondii was related to age [9,10]. Consistent with these studies, the present study showed highly significant differences in T. gondii seropositivity in the different age groups (18-45, 45-65, >65 years) in the two ethnic populations.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding demographic characteristics, the T. gondii seroprevalence found in the present study was not significantly associated with any of the sociodemographic characteristics of the psychiatric patients. It has been reported that seropositivity to T. gondii is related to age [11][12][13]; however, in the present investigation, T. gondii infection in psychiatric patients was not significantly influenced by age. Although high seropositivity to T. gondii was found in the 70-79 and 580 years age groups of psychiatric patients, the number of subjects in age groups 60-69, 70-79 and 580 years was limited in this study.…”
Section: Discussioncontrasting
confidence: 88%
“…One out of every three farmworker families consumed the infected meat of their animals. Consumption of infected animal meat might be a threat for toxoplasmosis transmission; it has been reported that tissue cysts are mostly detected in the intercostal, leg, and diaphragmatic muscles of sheep and poultry, which are frequently consumed by humans and have been implicated as an important source of toxoplasmosis [20,21] In this study, we found that increasing age was associated with the seropositivity of T. gondii, which was reported previously in other studies [22][23][24][25][26][27]. This might be explained by longer exposure to risk factors and by the transmission methods of T. gondii.…”
Section: Discussionsupporting
confidence: 84%